ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PERPAJAKAN WAJIB PAJAK DI SEKTOR PERIKANAN - Muhamad Nurkhamid; Christian Candrahadi Sandyputra (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2017)
Indonesia has a large economic potential in the fishery sector, yet it is not followed by a corresponding tax revenue from this sector. This study was conducted to examine the effect of tax knowledge, probability of tax audit, perception of government spending, penalties, financial constraints and referent group on tax compliance of non-employee private taxpayers in the fishery sector. This study used quantitative method through surveys conducted on samples in the provinces of Bali and DKI Jakarta. Data obtained from the survey’s results were tested by multiple regression analysis of Ordinary Least Square (OLS). The results of the tests conducted show that simultaneously, all factors tested have significant effect on tax compliance. Individually, tax knowledge, probability of tax audit and perception of government spending have positive and significant effect on tax compliance. Other factors, namely penalties, financial constraints and referent group have no significant effect on tax compliance